2014
DOI: 10.1542/hpeds.2013-0116
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Data Misclassifies and Fails to Identify Nephrotoxin-Associated Acute Kidney Injury in Hospitalized Children

Abstract: Objectives: Nephrotoxin exposure is a common cause of acute kidney injury (AKI) in hospitalized children. AKI detection relies on regular serum creatinine (SCr) screening among exposed patients. We sought to determine how well administrative data identify hospitalized noncritically ill children with nephrotoxic medication-associated AKI in the contexts of incomplete and complete screening. Methods: We conducted a single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Here, we report a much higher incidence of AKI of 50.9%, which likely reflects several factors. First, mild degrees of AKI are commonly overlooked and not recorded on the discharge summary (18,19). Second, we used a standardized definition of AKI, which undoubtedly led to increased recognition of AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report a much higher incidence of AKI of 50.9%, which likely reflects several factors. First, mild degrees of AKI are commonly overlooked and not recorded on the discharge summary (18,19). Second, we used a standardized definition of AKI, which undoubtedly led to increased recognition of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…None of these home medications were associated with higher risk of AKI on admission (ACE-I/ angiotensin-receptor blocker P=0.87; loop diuretic P=0.67; CNI P=0. 19).…”
Section: Aki Incidence and Risk Factorsmentioning
confidence: 99%
“…Ahmed et al noted that AKI detection was much more reliable than International Classification of Diseases Ninth Revision (ICD-9) coding for AKI. We have also observed that systematic surveillance for AKI yields higher AKI detection rates than reliance on ICD-9 coding for hospitalized children exposed to nephrotoxic medications (NTMx) [6].…”
Section: Acute Kidney Injury Detectionmentioning
confidence: 98%
“…Our understanding of medication-induced renal dysfunction is limited by current reporting systems that underestimate AKI (58). However, close attention is warranted with medications known to affect renal perfusion or glomerular filtration.…”
Section: S39mentioning
confidence: 99%